Redescription and evolutionary relationships of the Cuban endemic monotypic genus Holguinia Evans, 1955 (Lepidoptera, Hesperiidae, Hesperiinae). Issue 1 (14th August 2020) - Núñez, Rayner; Alegre-Barroso, Aylin; Hausmann, Axel
Abstract : We redescribe the Cuban endemic monotypic skipper genus Holguinia Evans and assess its phylogenetic position. Based on a 5640 bp dataset consisting of one mitochondrial and eight nuclear genes, we recovered Holguinia as a member of the Hesperiina, one of the subtribes of the mostly Neotropical Hesperiini, the largest tribe within the subfamily Hesperiinae. The ancestor of Holguinia split from continental relatives ∼15 Ma and likely reached the proto Cuban islands by dispersal over water. The genus seems to be one of the oldest Hesperiini lineages of our sampling and is not closely related to the other genera inhabiting the islands. Holguinia is also quite distinctive in its morphology. The underside of wings splashed with bright emerald scaling is unique among the Hesperiidae and the long ductus bursae of the female genitalia easily distinguish this genus from its close relatives.